Poisoning with methanol and other non-beverage alcohols - an analysis of the issue based on hospitalizations in department of toxicology - Sosnowska, Weronika; Brzozowska, Aleksandra; Tchórz, Michał; Radoniewicz–Tchórz, Anna; Tkaczyk, Rafał; Tomczyk, Jakub; Świątek, Gabriela; Trusz, Kornelia; Wanat, Iwona (Journal of Education, Health and Sport, 2023)
Introduction: Poisonings with non-beverage alcohols remain a significant problem in contemporary toxicology. Due to the large quantity and severe course of intoxications with methanol, the authors of this study focused primarily on poisonings with this substance. Methanol is widely used in industry. Its toxicity is attributed to its metabolites - formaldehyde and formic acid. Poisonings with methanol often lead to the patient’s death due to a wide range of complications associated with progressive metabolic acidosis. Material and Methods: The study is of a retrospective nature. It involved the analysis of medical records of patients admitted to the department of toxicology in 2022 after the consumption of non-beverage alcohols, with a particular focus on methanol. Data on the number of individuals admitted due to non-beverage alcohol intoxication between 2018 and 2022 was also analyzed. Results: Over the last 5 years (2018-2022), 36 individuals were hospitalized in the Clinical Toxicological-Cardiological Department due to non-beverage alcohol poisoning, with 16 (44.4%) cases involving methanol. In the year 2022, the department admitted 10 individuals aged 18 to 68, and 5 (50%) of them consumed methanol. Among the hospitalized, 90% were male, and 60% came from rural areas. Deliberate intoxications accounted for 70% of the cases. Four hospitalizations (40%) resulted in patient death. All deaths were associated with methanol intoxication. Conclusions: Non-beverage alcohol is often used by people with alcohol dependence syndrome. Among non-beverage alcohols, patients most often reached for methanol. Its consumption is associated with a high mortality rate and should be taken very seriously and treated immediately.